2016
DOI: 10.2147/dddt.s109080
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and relative bioavailability of fixed-dose combination of clopidogrel and aspirin versus coadministration of individual formulations in healthy Korean men

Abstract: BackgroundSimultaneous prescription of clopidogrel and low-dose aspirin is recommended for the treatment of acute coronary syndrome because of improvements in efficacy and patient compliance. In this study, the pharmacokinetics of a fixed-dose combination (FDC) of clopidogrel and aspirin was compared with coadministration of individual formulations to clarify the equivalence of the FDC.MethodsThis was a randomized, open-label, two-period, two-treatment, crossover study in healthy Korean men aged 20–55 years. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…A recent meta-analysis even showed that a high dose of ASA following coronary angioplasty was not associated with significantly higher cardiovascular death/MI/stroke or any major bleeding, implying that ASA alone might be safe to use [14]. In addition, a randomized open-label Korean study involving 60 healthy participants showed ASA and clopidogrel to have similar absorption profiles implying that both treatments were equally tolerated [15].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis even showed that a high dose of ASA following coronary angioplasty was not associated with significantly higher cardiovascular death/MI/stroke or any major bleeding, implying that ASA alone might be safe to use [14]. In addition, a randomized open-label Korean study involving 60 healthy participants showed ASA and clopidogrel to have similar absorption profiles implying that both treatments were equally tolerated [15].…”
Section: Discussionmentioning
confidence: 99%
“…All of these studies used the ABE approach for determining bioequivalence Three of these studies in Japanese and Korean subjects did not meet the bioequivalence standard for enteric-coated ASA, possibly because of the high variability of the drug [16,17,32]. Another study established bioequivalence in Korean men using the average bioequivalence (ABE) approach; however, the PK data for ASA indicated high intra-subject variability [33]. As no data from studies investigating the intra-individual variability of the primary PK parameters of enteric-coated ASA under fed condition have been reported, we assumed that the SD w was similar between the fasting and fed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…As no data from studies investigating the intra-individual variability of the primary PK parameters of enteric-coated ASA under fed condition have been reported, we assumed that the SD w was similar between the fasting and fed conditions. SD w was [ 0.294 for the C max of ASA [32][33][34] under fasting conditions [35]; hence, an RSABE analysis was conducted to assess the bioequivalence of the PK parameters of ASA with high intra-subject variability, which successfully established the bioequivalence of ASA in the ASA/clopidogrel FDC. Thus, the bioequivalence of ASA and clopidogrel FDC to co-administered individual formulations under fed conditions was established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a study with Korean subjects also did not meet the bioequivalence requirement [15]. The fourth study, performed with Korean subjects, established bioequivalence in Korean men using the average bioequivalence approach, though the data reported the pharmacokinetics of acetylsalicylic acid with high intrasubject variability [16].…”
Section: Discussionmentioning
confidence: 99%